Electrical resistivity of CuAlMo thin films grown at room temperature by dc magnetron sputtering. (29th July 2016) - Birkett, Martin; Penlington, Roger
Abstract: We report on the thickness dependence of electrical resistivity of CuAlMo films grown by dc magnetron sputtering on glass substrates at room temperature. The electrical resistance of the films was monitored in situ during their growth in the thickness range 10–1000 nm. By theoretically modelling the evolution of resistivity during growth we were able to gain an insight into the dominant electrical conduction mechanisms with increasing film thickness. For thicknesses in the range 10–25 nm the electrical resistivity is found to be a function of the film surface roughness and is well described by Namba's model. For thicknesses of 25–40 nm the experimental data was most accurately fitted using the Mayadas and Shatkes model which accounts for grain boundary scattering of the conduction electrons. Beyond 40 nm, the thickness of the film was found to be the controlling factor and the Fuchs–Sonheimer (FS) model was used to fit the experimental data, with diffuse scattering of the conduction electrons at the two film surfaces. By combining the Fuchs and Namba (FN) models a suitable correlation between theoretical and experimental resistivity can be achieved across the full CuAlMo film thickness range of 10–1000 nm. The irreversibility of resistance for films of thickness >200 nm, which demonstrated bulk conductivity, was measured to be less than 0.03% following subjection to temperature cycles of −55 and +125 °C and the temperature co-efficient of resistance was less than ±15 ppm °C −1 .